SLA-based content adaptation framework for optimizing QoE and energy consumption - Ismail, Mohd Norasri; Ibrahim, Rosziati; Md. Fudzee, Mohd Farhan; Jofri, Muhammad Hanif (Asian Research Publishing Network (ARPN), 2015)
Mobile device advancement and popularity has changed the way we consumed web content. However, the heterogeneity properties of mobile devices, subscribed network as well as its users lead to mismatch problem. The content adaptation system is the most viable solution for this issue. Most previous works in ADTE adapt the MPEG-21 Digital Item Adaptation (DIA) specification. However, only few work on optimizing energy consumption as well as quality of experience as a vision in Universal Multimedia Experience (UME). This paper proposes a framework of an adaptation decision-taking engine based on Service Level Agreement (SLA) and uses MPEG-21 Digital Item Adaptation specification. The SLA mechanism is integrated in this framework to enable more flexible decision-making process in the content adaptation system. This flexibility will support optimum QoE based on device current property status.